2019
DOI: 10.3389/fgene.2019.00091
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lncRNA–miRNA–mRNA Network to Reveal Potential Functional ceRNAs in Bovine Skeletal Muscle

Abstract: There is growing evidence that non-coding RNAs are emerging as critical regulators of skeletal muscle development. In order to reveal their functional roles and regulatory mechanisms, we constructed a lncRNA–miRNA–mRNA network according to the ceRNA (competitive endogenous RNA) theory, using our high-throughput sequencing data. Subsequently, the network analysis, GO (Gene Ontology) analysis, and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analysis were performed for functional annotation and explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 63 publications
2
37
0
Order By: Relevance
“…lncRNAs can be either single-exonic or multi-exonic, while it is a challenge to distinguish true lncRNAs from the abundant one exon, low expression fragments and expression noise assembled from RNA-Seq data (Cabili et al 2011;Derrien et al 2012). Thus, we only chose multi-exonic lncRNAs for further analysis, as was done in other studies (Tong et al 2017;Kern et al 2018;Yang et al 2018;Yue et al 2019), and depends on a highly stringent filtering pipeline to minimise the number of false-positive lncRNAs. Consequently, 4155 non-protein coding transcripts were considered as highly reliable lncRNAs, which was less than previous studies due to our stringent criteria (Billerey et al 2014;Liu et al 2017;Choi et al 2019;Yue et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…lncRNAs can be either single-exonic or multi-exonic, while it is a challenge to distinguish true lncRNAs from the abundant one exon, low expression fragments and expression noise assembled from RNA-Seq data (Cabili et al 2011;Derrien et al 2012). Thus, we only chose multi-exonic lncRNAs for further analysis, as was done in other studies (Tong et al 2017;Kern et al 2018;Yang et al 2018;Yue et al 2019), and depends on a highly stringent filtering pipeline to minimise the number of false-positive lncRNAs. Consequently, 4155 non-protein coding transcripts were considered as highly reliable lncRNAs, which was less than previous studies due to our stringent criteria (Billerey et al 2014;Liu et al 2017;Choi et al 2019;Yue et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we only chose multi-exonic lncRNAs for further analysis, as was done in other studies (Tong et al 2017;Kern et al 2018;Yang et al 2018;Yue et al 2019), and depends on a highly stringent filtering pipeline to minimise the number of false-positive lncRNAs. Consequently, 4155 non-protein coding transcripts were considered as highly reliable lncRNAs, which was less than previous studies due to our stringent criteria (Billerey et al 2014;Liu et al 2017;Choi et al 2019;Yue et al 2019). These lncRNAs have different expression distribution in different chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ceRNA theory indicates that lncRNAs act as sponge for miRNA to manipulate the expression of coding gene. 16 Therefore, identifying miRNA/mRNA that has a connection with DGCR5 will advance our understanding of the DGCR5 roles in NSCLC. Growing evidence has revealed that miRNAs play crucial roles in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…This ceRNA network was visualized using Cytoscape software (Version 3.6.0). [18] In this network, nodes and edges represented biological data in a direct manner in which each node represented a biological molecule, and the edges represented interactions between nodes. [19] LncRNAs, mRNAs, and miRNAs in the ceRNA network were presented as blue diamonds, green ellipses, and red triangles, respectively.…”
Section: Construction Of the Lncrna-mediated Cerna Networkmentioning
confidence: 99%